1978
DOI: 10.1002/lary.1978.88.5.787
|View full text |Cite
|
Sign up to set email alerts
|

The True Nature of Bell's Palsy: Analysis af 1,000 Consecutive Patients

Abstract: In a series of 1502 patients seen in our Facial Paralysis Research Clinic 1048 were diagnosed as having Bell's palsy. Review of clinical, epidemiologic, and laboratory data, plus review of the literature, has led to the conclusion that Bell's palsy is an acute benign cranial polyneuritis probably caused by reactivation of the herpes‐simplex virus, and the dysfunction of the motor cranial nerves (V, VII, X) may represent inflammation and demyelinization rather than ischemic compression. Spinal fluid analysis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
214
6
7

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(247 citation statements)
references
References 24 publications
17
214
6
7
Order By: Relevance
“…May 11 found otalgia in 50% of the patients, paresthesia in 40% and viral prodrome in 60%. Adour 3 reported 20% viral prodrome, 10% headache and 32% facial paresthesia in the study with 515 patients. According to Fortes and Rego 12 and Furuta 13 , insult to the nerve could be resultant from the reactivation of the latent nerve located in axons and nervous endings, triggering inflammation and infection in adjacent cells after a trauma, exposure to aggressive environmental factors or metabolic and/or emotional affections.…”
Section: Graphmentioning
confidence: 82%
See 1 more Smart Citation
“…May 11 found otalgia in 50% of the patients, paresthesia in 40% and viral prodrome in 60%. Adour 3 reported 20% viral prodrome, 10% headache and 32% facial paresthesia in the study with 515 patients. According to Fortes and Rego 12 and Furuta 13 , insult to the nerve could be resultant from the reactivation of the latent nerve located in axons and nervous endings, triggering inflammation and infection in adjacent cells after a trauma, exposure to aggressive environmental factors or metabolic and/or emotional affections.…”
Section: Graphmentioning
confidence: 82%
“…Adour et al 3 , assessed 1,048 patients and did not observe any difference among genders, but the frequency was twice higher in female patients aged 10 to 19 years, and 1.5 times higher in male patients aged over 40 years. Devriese et al 4 did not find predominance between genders in their study with 1,293 cases.…”
Section: Graphmentioning
confidence: 93%
“…It is said to be a virally mediated cranial neuritis. The probable etiological agent is Herpes simplex virus type I [7]. Other causes proposed include autoimmune, allergy, infectious agents, cold, and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Bell's Palsy causes consider able functional, psychosocial and aesthetic disturbance to patients. Histological and clinical evidence suggests that the site of lesion within the confluence of the facial canal, particularly at its medial end [3] . However, most recent studies have shown that herpes simplex virus 1 may be the most likely candidate virus and polymerase chain reaction of endoneurial fluid Herpes simplex virus 1 genome has been identified in more than three quarter of bell's palsy cases, whereas varicella zoster virus or Epstein barr virus have not been found therein [4,5,7,21] .…”
Section: Introductionmentioning
confidence: 99%